Knowledge, attitude, and practice regarding stone formation and recurrence among urolithiasis patients: a cross-sectional study - Tieding Chen; Yan Jiang; Peng Zhang; Fang Wang; Bangbin Chen; Dianjun Yu (Scientific Reports)
Abstract This study investigated the knowledge, attitude, and practice (KAP) concerning stone formation and recurrence among patients with urolithiasis treated at Ningbo Medical Centre Lihuili Hospital between August 19, 2023, and April 19, 2024. A total of 394 patients were included, among which 70.30% were males. The median scores for knowledge, attitude, and practice were 7 (6-8.25), 29 (26.75-31), and 21.5 (18–25), respectively, indicating good knowledge and attitude but suboptimal practice. Positive correlations were found between knowledge and attitude (r = 0.274, P < 0.001) and between attitude and practice (r = 0.126, P < 0.05). Logistic regression revealed that knowledge, education, and whether the patient experienced a new or recurrent stone were independent predictors of attitude. Attitude, education, body mass index (BMI), and daily water intake were independent predictors of practice. Structural equation modeling (SEM) showed that knowledge, family history, and education directly influenced attitude, while education also significantly impacted practice. Our findings highlight the need for targeted diet, hydration, and lifestyle education to enhance preventive practices among patients with urolithiasis.